Sex Hormones, Sleep, and Memory: Interrelationships Across the Adult Female Lifespan - Harrington, Yasmin A.; Parisi, Jeanine M.; Duan, Daisy; Rojo-Wissar, Darlynn M.; Holingue, Calliope; Spira, Adam P. (Frontiers in Aging Neuroscience, 2022)
As the population of older adults grows, so will the prevalence of aging-related conditions, including memory impairments and sleep disturbances, both of which are more common among women. Compared to older men, older women are up to twice as likely to experience sleep disturbances and are at a higher risk for cognitive decline and Alzheimer’s disease and related dementias (ADRD). These sex differences may be attributed in part to fluctuations in levels of female sex hormones (i.e., estrogen and progesterone) that occur across the adult female lifespan. Though women tend to experience the most significant sleep and memory problems during the peri-menopausal period, changes in memory and sleep have also been observed across the menstrual cycle and during pregnancy. Here, we review current knowledge on the interrelationships among female sex hormones, sleep, and memory across the female lifespan, propose possible mediating and moderating mechanisms linking these variables, and describe implications for ADRD risk in later life.